PROPUESTA DE IMPLEMENTACION DE UN SISTEMA DE GESTION DE CALIDAD ISO 9001:2008 EN UNA EMPRESACOMERCIAL - Huamán Mejía, María Celina (2011)
The use of quality management systems are a global trend, as organizations from different economic sectors are engaged in their process of certification or recertification in many cases. ISO standards, since its publication in 1987 caused a major impact on trade of nations, and thanks to this and other trade rules, the actors national and international companies can rely on this certification bearing as normalized requirements, terms and commercial properties. The commercial sector has been growing in recent years, in 2008 came to 13.1% compared to 9.7% achieved in 2007 with respect to its share of GDP of Peru. That is why the importance of this sector, without neglecting the employment it provides, and which holds 30% of the labor market. The goal is to design a proposal for implementation of a Quality Management System ISO 9001:2008 for a commercial enterprise. METHODOLOGY: Model will own the Quality Management System ISO 9001: version 2008. This research aims to provide a guideline to companies in the commercial sector on their way to the normalization of their services and to demonstrate the positive impact of ISO 9001-2008 Management Systems business processes.